2003
DOI: 10.1104/pp.014712
|View full text |Cite
|
Sign up to set email alerts
|

Phloem-Localizing Sulfate Transporter, Sultr1;3, Mediates Re-Distribution of Sulfur from Source to Sink Organs in Arabidopsis

Abstract: For the effective recycling of nutrients, vascular plants transport pooled inorganic ions and metabolites through the sieve tube. A novel sulfate transporter gene, Sultr1;3, was identified as an essential member contributing to this process for redistribution of sulfur source in Arabidopsis. Sultr1;3 belonged to the family of high-affinity sulfate transporters, and was able to complement the yeast sulfate transporter mutant. The fusion protein of Sultr1;3 and green fluorescent protein was expressed by the Sult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(136 citation statements)
references
References 31 publications
5
126
2
3
Order By: Relevance
“…Judging from the close sequence similarities with other functional sulfate transporters in plants (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 1997Takahashi et al, , 2000Vidmar et al, 1999Vidmar et al, , 2000Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003), it is suggested that SULTR4;1 and SULTR4;2 belong to the proton/ sulfate cotransporter family and may use DpH across the tonoplast as a motive force for the efflux of sulfate. Database searches found several other SULTR4 transporters in various plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Judging from the close sequence similarities with other functional sulfate transporters in plants (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 1997Takahashi et al, , 2000Vidmar et al, 1999Vidmar et al, , 2000Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003), it is suggested that SULTR4;1 and SULTR4;2 belong to the proton/ sulfate cotransporter family and may use DpH across the tonoplast as a motive force for the efflux of sulfate. Database searches found several other SULTR4 transporters in various plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sultr1;2 mutant showed accumulation of SULTR2;1 mRNA (Maruyama-Nakashita et al, 2003), suggesting that the internal transport of sulfate was activated in response to the loss of sulfate uptake in the mutant. Further studies identified the role of SULTR1;3 as a functional sulfate transport system involved in phloem transport of sulfate (Yoshimoto et al, 2003). Taken together, the members of the sulfate transporter gene family appear to have distinctive cell type specificities and are regulated by sulfur availability to optimize both uptake and internal transport under varying sulfur availability.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of marker genes, RbcS for mesophyll cells and Sultr for vascular bundles (Yoshimoto et al, 2003), was examined to further confirm that the separation of the tissues was efficient ( Figure 8C). The expression of RbcS in mesophyll protoplasts was approximately four times higher than that in the vascular bundle samples.…”
Section: Isolation Of Mesophyll Cells and Vascular Bundlesmentioning
confidence: 99%
“…Past attempts to modify plants transgenically to express FP membrane protein fusions in SEs (Lalonde et al, 2003;Yoshimoto et al, 2003;Stadler et al, 2005) have resulted in retention of the fluorescence signal in CCs. At the same time, of course, a wide variety of integral membrane proteins are known and expected to be found in SEs.…”
Section: Expression Of the Sumcr Construct Yields An Mcitrine Signal mentioning
confidence: 99%